Sleeve lobectomy versus pneumonectomy for non-small cell lung cancer: a meta-analysis - Shi Woda; Zhang Wei; Sun Haoliang; Shao Yongfeng (World Journal of Surgical Oncology, 2012)
Abstract Aim It is controversial that whether sleeve lobectomy (SL) should be promoted more worthy than pneumonectomy (PN) in suitable patients. Methods We searched all studies that had been published in English from PUBMED and Embase which compared the short-term and long-term outcomes of SL and pneumonectomy (PN) in patients with non-small cell lung cancer (NSCLC). Results Nineteen studies met our criteria with a combined total of 3878 subjects, of which 1316 (33.9%) underwent SL and 2562 (66.1%) underwent PN. The odds ratio was 0.50 (95% CI: 0.34-0.72) for postoperative mortality, 1.17 (95% CI: 0.82-1.67) for postoperative complications, 0.78 (95% CI: 0.47-1.29) for locoregional recurrences. The risk difference for 1-, 3-, 5- year was 0.11 (95% CI: 0.07-0.14), 0.15 (95% CI: 0.06-0.24), 0.15 (95% CI: 0.09-0.20),respectively. The pooled hazard ratio was 0.63 (95% CI: 0.56-0.71) in favor of SL group. Conclusion SL is more worthy to be done than PN in suitable patients with less mortality and better long-term survival.